1996
DOI: 10.1287/trsc.30.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance and Crew Considerations in Fleet Assignment

Abstract: Given a flight schedule, which is a set of flight segments with specified departure and arrival times, and a set of aircraft, the fleet assignment problem is to determine which aircraft type should fly each flight segment. The objective is to maximize revenue minus operating costs. In the basic fleet assignment problem considered by Hane et al. (Hane, C. A., C. Barnhart, E. L. Johnson, R. E. Marsten, G. L. Nemhauser, G. Sigismondi. 1995. The fleet assignment problem: Solving a large-scale integer program. Math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(74 citation statements)
references
References 7 publications
0
74
0
Order By: Relevance
“…Each aircraft's rotation visits maintenance stations at regular intervals. More details on the maintenance routing problem are contained in Feo and Bard (1989), Gopalan and Talluri (1998), and Clarke et al (1996b). For restricted maintenance routings of three or four days, Gopalan and Talluri (1998) and describe graph-theoretic approaches to maintenance routing.…”
Section: Aircraft Maintenance Routingmentioning
confidence: 99%
“…Each aircraft's rotation visits maintenance stations at regular intervals. More details on the maintenance routing problem are contained in Feo and Bard (1989), Gopalan and Talluri (1998), and Clarke et al (1996b). For restricted maintenance routings of three or four days, Gopalan and Talluri (1998) and describe graph-theoretic approaches to maintenance routing.…”
Section: Aircraft Maintenance Routingmentioning
confidence: 99%
“…Nonetheless, airline schedule planners have keen interest in improving upon the sequential solution approach, with its costly impact on crew scheduling. Clarke et al (1996a) and Barnhart et al (1998a) have taken steps towards integrating fleet assignment and crew scheduling by modifying fleet assignment models to account for some of the downstream effects on crews. Clarke et al (1996a) include bonuses for fleet assignments that allow crews to stay with the same aircraft.…”
Section: Integrating Core Modelsmentioning
confidence: 99%
“…Clarke et al (1996a) and Barnhart et al (1998a) have taken steps towards integrating fleet assignment and crew scheduling by modifying fleet assignment models to account for some of the downstream effects on crews. Clarke et al (1996a) include bonuses for fleet assignments that allow crews to stay with the same aircraft. This reduces the occurrence of extended periods of crew rest between flights (the fleet assignment objective indirectly works to achieve solutions with high aircraft utilization), thereby eliminating unnecessary crew inactivity and costs.…”
Section: Integrating Core Modelsmentioning
confidence: 99%
“…Hane et al [10] use a similar multicommoditv network flow formulation to solve the basic fleet assignment problem, but their use of variable aggregation, cost perturbations, dual simplex with steepest-edge pricing, and intelligent branch-and-bound strategies result in a rapid solution to realistically-sized (2500-flight, eleven-fleet) problems. Gu et al [9] study the complexity and behavior of the model presented in the Hane paper, while in Clarke et al [4], a sequel to the Hane paper, it is shown that better operational solutions to the fleet assignment problem can be achieved by adding variables and constraints that model maintenance and crew issues.…”
Section: Literature Reviewmentioning
confidence: 99%